2016
DOI: 10.1111/echo.13290
|View full text |Cite
|
Sign up to set email alerts
|

Is dipyridamole useful in improving left ventricular systolic and diastolic function in patients with coronary slow flow?

Abstract: Left ventricular systolic and diastolic function may be negatively affected by CSF. Dipyridamole may improve these functions, especially at the tissue level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…They showed that microvascular dysfunction partially normalizes after intracoronary infusion of dipyridamole. Similarly, Suner and Cetin 29) reported DD to improve in patients with CSFP treated with dipyridamole for 2 months.…”
Section: Discussionmentioning
confidence: 79%
“…They showed that microvascular dysfunction partially normalizes after intracoronary infusion of dipyridamole. Similarly, Suner and Cetin 29) reported DD to improve in patients with CSFP treated with dipyridamole for 2 months.…”
Section: Discussionmentioning
confidence: 79%
“…These conclusions are of great interest. Indeed, as the same authors reported in the discussion section, different results had been obtained before by other research groups in the same kind of patients,[ 8 9 10 11 ] who found an impaired diastolic function in patients with CSF, assessed with conventional parameters and with 2D STE analysis. Particularly, Wang et al .…”
mentioning
confidence: 72%
“…These results seem to be in line with the findings reported by Sezgin et al . [ 10 ] and Suner and Cetin[ 11 ] who found a reduced LV diastolic function and a normal systolic function. Of course, Fallah et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the treatments for CSF mainly include enhancement of microcirculation, protection of the vascular endothelium, anti-in ammatory treatment, and atherosclerosis inhibition. Drugs such as Statins [21], Nebivolol [22], Dipyridamole [23], Calcium channel blockers [24][25], Trimetazidine[26] and Nikodir [27] have been proven clinically effective for CSF. Coronary angiography(CAG) is the only effective way to diagnose CSF.…”
Section: Introductionmentioning
confidence: 99%